The Effect of Physical Education to Improve Motor Competence of Elementary School Children - Pulung Riyanto; Syamsudin Syamsudin (JUARA : Jurnal Olahraga, 2021)
This study aimed to determine the effect of physical education in improving children's motor competence in primary schools. To enhance children's motor competence, the research method used was a quasi-experimental method with The Pretest Post-Test Two Treatment Design. The sample used was elementary school students in Merauke District with a total of 60 people. The instrument used is using Somatic measures (measuring the height, weight, BMI, and thickness of the student's fat). Then the second test instrument uses Motor skills (Gymnastics skills, Soccer skills, Basketball skills, Track-and-field skills). The results showed that the physical education program could improve the motor competence of elementary school children, as for the conclusion of this study that physical education programs provided in elementary schools can improve children's motor competence. This increase is inseparable from a physical education program that is well designed and by the child's characteristics.